ANALISIS KOMPETENSI SOSIAL GURU BERDASARKAN SERTIFIKAT PENDIDIK - Anisya Islami; Neni Hermita; Jesi Alexander Alim (Jurusan Ilmu Pendidikan, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Riau, 2022)
The research aims to know teachers’ social competences based on the educator certificate. The research method used in this study is a descriptive quantitative method. The data-collection technique used was a questionnaire technique. The data analysis technique used is a descriptive analysis. Teachers’ social competences based on educator certificates in general have a good category. This corresponds with teachers’ social competence indicators of being inclusive and objective, adapting to the assigned environment, effective communication and good manners in communication.